Absolutely Maybe - Yee, Lisa (Arthur A. Levine Books, 2009)
When living with her mother, an alcoholic ex-beauty queen, becomes unbearable, almost seventeen-year-old Maybelline "Maybe" Chestnut runs away to California, where she finds work on a taco truck and tries to track down her birth father.